Prevalence of illicit drug use among the Italian athlete population with special attention on drugs of abuse: A 10-year review - Strano Rossi, S.; Botre, F. (Journal of Sports Sciences, 2011)
The objective of this study was to assess the prevalence of illicit drugs use among young adults, in particular elite athletes. This study considers the data obtained from anti-doping analyses performed on nearly 100,000 urine samples from 2000 to 2009 by the World Anti-Doping Agency accredited Italian Anti-Doping Laboratory. The percentage of adverse analytical findings varies on a yearly basis, but it is in the range 1.0-1.8% (not considering atypical findings, such as an altered endogenous steroid profile). Among positive results, there is a high prevalence of stimulants and drugs of abuse. The drug of abuse found most frequently is the tetrahydrocannabinol (cannabis) metabolite, accounting for 0.2-0.4% of the total samples analysed (18% of the positive results). The second most frequently encountered drug is cocaine, as detected from cocaine metabolites, accounting for 0.1% of the total samples analysed (7% of positive results). Other stimulants found included amphetamines, ephedrines, carphedon, modafinil, and anorexic compounds. No amphetamine-like designer drugs were detected. These data are indicative of the widespread prevalence of cocaine and cannabis use among the young adult population. However, due to the particular population studied, it must be considered an underestimation of the phenomenon among elite athletes with respect to the general population.